2004
DOI: 10.1158/1078-0432.ccr-03-0828
|View full text |Cite
|
Sign up to set email alerts
|

A Concentrated Aglycone Isoflavone Preparation (GCP) That Demonstrates Potent Anti-Prostate Cancer Activity In vitro and In vivo

Abstract: Purpose: Isoflavones have anticancer activities, but naturally occurring isoflavones are predominantly glycosylated and poorly absorbed. Genistein combined polysaccharide (GCP; Amino Up Chemical Co., Sapporo, Japan), is a fermentation product of soy extract and basidiomycetes mycillae that is enriched in biologically active aglycone isoflavones. This study analyzes GCP in vitro and in vivo for potential utility as a prostate cancer chemopreventative agent.Experimental Design: Androgen-sensitive LNCaP and andro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 41 publications
7
60
1
2
Order By: Relevance
“…15,[21][22][23][24] Feeding mice with soy phytochemical concentrate (SPC, containing genistein, daidzein and glycitein) or an aglycone isoflavone preparation reduced tumor growth of s.c. implanted human LNCaP cells in immunocompromised mice. 15,22 In a prevention study of Zhou et al, 23 using an orthotopic model of LNCaP cells in SCID mice similar to our model, SPC was more effective than genistein or soy protein. This prevention study is in agreement with the efficacy demonstrated by soy isoflavones in our therapeutic study of established prostate tumors.…”
Section: Discussionmentioning
confidence: 99%
“…15,[21][22][23][24] Feeding mice with soy phytochemical concentrate (SPC, containing genistein, daidzein and glycitein) or an aglycone isoflavone preparation reduced tumor growth of s.c. implanted human LNCaP cells in immunocompromised mice. 15,22 In a prevention study of Zhou et al, 23 using an orthotopic model of LNCaP cells in SCID mice similar to our model, SPC was more effective than genistein or soy protein. This prevention study is in agreement with the efficacy demonstrated by soy isoflavones in our therapeutic study of established prostate tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The cultures were prepared in quadruplicate for each afzelin concentration and time point, and maintained in a CO 2 incubator for three days. After 24, 48 and 72 h, 10 µl water soluble tetrazolium salt (WST)-1 labeling solution (WST-1 cell proliferation assay kit; Roche Diagnostics, Indianapolis, IN, USA) was added to the cultures and the cells were returned to the CO 2 incubator for 2 h (19). The specific type of formazan product formed was detected by measuring its absorbance in a 96-well spectrophotometric plate reader (DiaSorin, Stillwater, MN, USA) at a wavelength of 420 nm, as described by the manufacturer (20).…”
Section: Methodsmentioning
confidence: 99%
“…In many different cell lines and xenografts, the tyrosine kinase inhibitory characteristics of genistein induce apoptosis, cell-cycle arrest, hinders proliferation, prevents angiogenesis, and blocks androgen and estrogen-stimulated transcription. [56][57][58][59][60] In addition, studies demonstrate genistein may oppose many cellular survival mechanisms induced by radiation, chemotherapy or androgen deprivation, suggesting the usefulness of this agent as adjunctive therapy. 61,62 Subsequent analysis of these favorable biochemical changes reveal that many of them are mediated through Akt pathways (see Figure 1).…”
Section: Inhibition Of Akt Pathways Ec Nelson Et Almentioning
confidence: 99%
“…Concentrated aglycone-rich food supplements, such as genistein combined polysaccharide (GCP), may allow higher plasma levels of isoflavones. 58 Recently, a prospective randomized study by Rannikko et al 65 found that prostate tissue concentrates phytoestrogens including genistein, thus suggesting that plasma concentrations underestimate tissue concentrations by over 50%.…”
Section: Inhibition Of Akt Pathways Ec Nelson Et Almentioning
confidence: 99%